The response of oil palm seedlings' growth to vermicompost and water stress under the main nursery stage - Kautsar, Valensi; Ismawanto, Diky; Dyah Ully Parwati, Wiwin (Jurnal Online Pertanian Tropik, 2023)
The availability of nutrients and water are two things that are essential for the development of plants. Future oil palm agriculture will require a strategy for the management of water because of the erratic nature of the weather. The addition of organic matter, such as vermicompost, is one strategy for addressing the issue of insufficient water supplies. The primary objective of this study is to investigate the relationship between oil palm seedlings' exposure to vermicompost and various levels of water stress in the main nursery. During the three-month study, 100, 200, and 300 g of vermicompost per polybag was combined with 1.0, 1.5, and 2.0 L/polybag/day. There was no relationship between the dose of vermicompost and the water stress that had observed. The addition of 300 g/polybag of vermicompost increased root fresh weight by 37.8% compared to 100 g/polybag. Moreover, water stress leads to a reduction in plant height and dry weight of the shoots. Compared to 2 L/polybag/day, plant height was lowered by 23.3% and 19.8% at watering volumes of 1.0 and 1.5 L/polybag/day, respectively. In addition, when compared to the appropriate water level of 2 L/polybag/day, high water stress (1.0 L/polybag/day) declined shoot dry weight by 12%.